DETERMINANTS OF BANKING CREDIT DEFAULT IN INDONESIA: A COMPARATIVE ANALYSIS - Imaduddin, Muhammad (Al-Infaq: Jurnal Ekonomi Islam, 2011)
Departing from the model developed by Jimẽnez and Saurina (2006), this study aims to analyse the determinants of Islamic banking credit default compared with conventional banking in Indonesia. This study utilised time-series analysis, by which ordinary least square method is adopted. 40 monthly data observations from January 2003 until April 2006 are used. The study is divided into two models, namely Islamic banking model and conventional banking model. The values of non-performing financing (NPF) in Islamic banking and nonperforming loan (NPL) in conventional banking are treated as the dependent variables. The results showed that two-month lagged of non-performing financing (NPF), total asset (ASSET), the amount of third-party-funds (TPF), one-month lagged of total financing (DFIN),and growth of gross-domestic product (GDPG) variables have significant impact to the ratio of non-performing financing (NPF) in Islamic banking. Meanwhile, the three-month lagged of non-performing loan (DDDNPL), total asset (CASSET), three-month as well as two-month period lagged of total loan (DDDCRED and DDCRED), inter-bank money market (PUAB), and growth of gross-domestic (GDPG) are significant to influence the ratio of non-performing loan (NPL) in conventional banking. The result also implied that the general election in 2004 had a significant influence to the ratio of non-performing financing (NPF) in Islamic banking. Eventough from the outset, it seems Islamic banking has a better performance than conventional banking by having a relatively low NPF, this study, however, has found the opposite. Albeit, Islamic banking showing a good long-run as well as short-run dynamics among all variables in the beginning, after modifying the model into autoregressive in the main analysis, results showed that conventional banking has a better performance than Islamic banking with higher correlation of determination. In this regard, we cannot assume that Islamic banking is performing poorly in managing credit default problems. This isbecause the result implied that the level of Islamic banking’s R-squared, R-bar-squared and DW values are good. Therefore, although Islamic banking is relatively a new comer in the Indonesian banking industry, it has shown a good performance in the banking credit risk management and can compete head-on with conventional banking, respectively.